Zinc uptake and loss in Corbicula Manilensis Philippi and its relation to water and sediment zinc concentrations. - Doronia, Nerissa Andrada (Quezon City, 1987)
Samples of Corbicula manilensis were collected from a segment of Angat River situated in Poblacion, Plaridel, Bulacan. The samples were acclimated and cultured in the laboratory in 20-liter tanks with aerated water and sediment from the source of the clam. In the uptake study, clam samples were exposed to 0, 5, 15 and 30 mg 1 raised to -1 of zinc as zinc sulfate for 29 days.
The zinc concentrations in water decreased with time following a two-phase process of zinc loss: a rapid initial phase within 0-7 days and a later slower phase. The zinc concentration in the sediment, on the other hand, logarithmically increased with time. Concentration of zinc in sediment was observed to be negatively correlated with the zinc concentration in the water. Zinc concentration in clam samples was shown to be more strongly correlated with zinc concentration in water. The elevated concentration of zinc in soft parts on day 3 may be attributed to the significantly high zinc concentration in water during the same period. A low correlation coefficient between the zinc concentrations in soft parts and sediment was obtained except on day 29 in which the increase in zinc concentration in soft parts may be a function of the zinc in sediment.
When the remaining clam samples were transferred to clean water for 22 days after day 29 of the uptake experiment, there was a slow process of zinc depuration in soft parts, and even slower process of zinc elimination from the shells. The rate of zinc depuration was dose-dependent, i.e., clam soft parts exposed to higher treatments have correspondingly higher rates of zinc depuration. In shells, the zinc immediately eliminated in the process of exposure to clean water is believed to represent the zinc adsorbed on the shells while those that persisted could have been incorporated in the shells by growth.
This work also showed that gut may contain a variable and significant amount of zinc only during the early phase of the uptake experiment when zinc concentration in water is still high.
Finally, this investigation shows indication for the possible use of C. manilensis as a zinc biomonitor. The zinc concentration in clam soft parts was shown to respond rapidly to the increasing levels of zinc in the environment, particularly in water, indicating its potential as a short-term monitor of ambient levels of zinc. The shell zinc concentartion could be a potential indicator of total history of exposure based on the result of slow depuration.
Masteral thesis (Master of Science in Biology) -- University of the PHilippines, Diliman.
Keywords: Zinc toxicity -- Clams